NEGOTIATING SOCIAL IDENTITY THROUGH QUESTIONS IN CASUAL CONVERSATIONS: A CRITICAL DISCOURSE ANALYSIS - Sakhiyya, Zulfa (Universitas Pendidikan Indonesia, 2017)
Questioning is a potential means to establish identity in social interaction, and thus it helps position oneself in relation to others. However, this relationship between question and social identity remains relatively under-explored in the theoretical territory (Kao Weng, 2012; Tracy Naughton, 1994). This paper contributes to this area of inquiry by employing critical discourse analysis in investigating the construction and negotiation of social identity through questions. Data are drawn from four sets of casual conversations I conducted with two native and two non-native speakers of English. Two stages of analysis are carried out. Firstly, I present and distribute the questioning patterns that emerge from the conversation. Secondly, I analyse the questioning process and its relation to the negotiation of social identity. Findings and discussion reveal that social identity is multiple: as a site of struggle and subject to change. The negotiation of identity through questions is evident from the emerging patterns of the length of interrogative form, repetitive questions, and the intensity of social control.